Zeitgeschichte als Streitgeschichte : große Kontroversen nach 1945 - Sabrow, Martin 1954- Hrsg; Jessen, Ralph 1956- Hrsg; Große Kracht, Klaus 1969- Hrsg (Beck'sche Reihe, 2003)
Große Kontroversen seit 1945